2009
DOI: 10.2478/s11756-009-0037-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between arrival date, hatching date and breeding success of the white stork (Ciconia ciconia) in Slovakia

Abstract: Changes in the spring arrival dates of migrant birds have been reported from a range of locations and many authors have focused on long-term trends and their relationship to temperature and other climatic events. Perhaps more importantly, changed arrival dates may have consequences for the breeding dates of birds which strongly influence breeding success. In this paper we take the opportunity provided by a monitoring scheme of the white stork (Ciconia ciconia) to examine several features of the timing of arriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 11 publications
2
23
1
Order By: Relevance
“…In a Spanish population, a similar relationship was revealed, but it was fully accounted for by the age differences between storks arriving to their breeding territories at different times of the season (Vergara, Aguirre & Fernández-Cruz 2007). In contrast, no significant relationship was found between arrival dates and breeding success in a Slovakian population of White Storks (Fulin et al 2009). This may suggest that the benefits and costs of early arrival at breeding grounds could vary between populations and also from one year to another.…”
mentioning
confidence: 79%
“…In a Spanish population, a similar relationship was revealed, but it was fully accounted for by the age differences between storks arriving to their breeding territories at different times of the season (Vergara, Aguirre & Fernández-Cruz 2007). In contrast, no significant relationship was found between arrival dates and breeding success in a Slovakian population of White Storks (Fulin et al 2009). This may suggest that the benefits and costs of early arrival at breeding grounds could vary between populations and also from one year to another.…”
mentioning
confidence: 79%
“…In our study area, first nest occupation dates were much earlier than arrival dates reported in European regions (Barbraud et al 1999;Ptaszyk et al 2003;Gordo and Sanz 2008;Fulin et al 2009;Kosicki 2010). Presumably, White Storks from North African populations arrive earlier on their breeding grounds because migratory distances from wintering areas are shorter compared to the routes followed by European populations (Géroudet 1978;Gordo et al 2013).…”
Section: Breeding and Growth Parametersmentioning
confidence: 47%
“…In spite of this, individuals that return early at breeding grounds are able to favourably match their timing of reproduction to the seasonally changing photoperiod. The first storks from the Central European population arrive at breeding grounds at the end of March (Tryjanowski and Sparks 2008;Janiszewski et al 2013), start breeding in the first half of April, and the chicks hatch at the beginning of May (Fulin et al 2009;Kosicki and Indykiewicz 2011). Under such a reproductive schedule, the increasing food demands of growing offspring are accompanied by increasing day length, and the moment of fledging may coincide with maximum lengths of daylight around the summer solstice.…”
Section: Discussionmentioning
confidence: 99%
“…The entire reproductive cycle, from egg laying to fledging of chicks takes about 3 months in this species (Schulz 1998). This implicates that early-arriving individuals, which usually start nesting by mid-April, may conclude their reproductive activities around the end of June (Fulin et al 2009), which is a period of maximal day lengths at temperate latitudes. However, large numbers of storks arrive at breeding grounds in Central Europe only in the second half of April or even at the beginning of May (Janiszewski et al 2013).…”
Section: Introductionmentioning
confidence: 95%